A implantação de uma nova estrutura organizacional em Colégios Maristas: equilíbrios e tensões entre a tradição e a modernidade - Anele, Clara Rimolo (Universidade do Vale do Rio dos Sinos, 2020)
This research has as its theme the study of the implantation of a new organizational structure in Marist schools, approaching balances and tensions between tradition and modernity. From this concern, the following research question was generated: how the new organizational structure implemented in the Marist Network contributed to more efficient administrative, pedagogical, and pastoral processes? The main objective of this study is to analyze how the new organizational structure contributed to the management and planning of processes in the administrative, pedagogical and pastoral spheres in two Marist schools, through a qualitative and quantitative approach of a descriptive nature, having as a strategy the case study. The gathering of data included documentary research, through semi-structured interviews and questionnaires application, in addition to data collection in an electronic system related to three internal indicators. The study sought to describe, through a comparative perspective, the main points between the previous structure and the new organizational structure; and to analyze how the changes to the new organizational structure reflected on the management, planning and internal indicators of strategic planning. The analyzed schools were chosen because they were the first ones to change the organizational structure and the management model, and because they had the largest number of students among the Marist schools in the city in which the study was conducted. In order to achieve the aforementioned goals, the concepts of organizational structure, school management, planning, corporate governance, and efficiency and effectiveness were studied. The theoretical framework was based on the following authors: Daft (2008), Murad (2012), Lück (2007), Oliveira (2015), Andrade and Rossetti (2009), Sander (2007), Gil (2010), among others. The results of this research suggest an improvement in administrative and pedagogical processes, both in theory and in practice, based on the new organizational model. However, according to the analysis, there is an opportunity for greater integration and inter-relation between these processes and pastoral dynamics. As an intervention proposal, the study suggested to develop the alignment of processes, in order to make them more feasible, in addition to emphasis on pastoral processes, promoting a necessary articulation between pastoral-pedagogical and administrative matters.
Keywords: Estrutura organizacional; Gestão; Governança; Educação básica; Redes privadas de educação; Organizational structure; Management; Governance; Basic education; Private education networks; ACCNPQ::Ciências Humanas::Educação